2016
DOI: 10.1099/ijsem.0.001155
|View full text |Cite
|
Sign up to set email alerts
|

Agarivorans aestuarii sp. nov., an agar-degrading bacterium isolated from a tidal flat

Abstract: A Gram-reaction-negative, aerobic, non-spore forming, rod-shaped bacterium motile with a single polar flagellum, designated strain hydD622 T , was isolated from the sediment of a tidal flat at Asan Bay, Korea. Strain hydD622 T exhibited an agarolytic activity. Comparison of 16S rRNA gene sequences revealed that strain hydD622 T was closely related to Agarivorans litoreus KCTC 42116 T , Agarivorans albus KCTC 22256 T and Agarivorans gilvus KCTC 32555 T with similarities of 98.4, 98.0 and 96.5 %, respectively. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Likewise, Glaciecola agarilytica dominated an agar-degrading community ( Wietz et al, 2015 ) in accordance with the agarolytic phenotype reported for this bacterium ( Yong et al, 2007 ). Several other genera within the Alteromonadaceae family have been connected with agarolytic activities such as Agarivorans ( Kim et al, 2016 ), Gayadomonas ( Chi et al, 2013 ), and Catenovulum ( Yan et al, 2011 ), however, little is known about the responsible enzymatic systems within these taxa. Paraglaciecola hydrolytica S66 T represents a newly isolated Gammaproteobacterium of the Alteromonadaceae family, which has the ability to degrade both agar and carrageenan ( Bech et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Glaciecola agarilytica dominated an agar-degrading community ( Wietz et al, 2015 ) in accordance with the agarolytic phenotype reported for this bacterium ( Yong et al, 2007 ). Several other genera within the Alteromonadaceae family have been connected with agarolytic activities such as Agarivorans ( Kim et al, 2016 ), Gayadomonas ( Chi et al, 2013 ), and Catenovulum ( Yan et al, 2011 ), however, little is known about the responsible enzymatic systems within these taxa. Paraglaciecola hydrolytica S66 T represents a newly isolated Gammaproteobacterium of the Alteromonadaceae family, which has the ability to degrade both agar and carrageenan ( Bech et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Agarivorans was initially proposed by Kurahashi and Yokota in 2004 ( 1 ).Currently, this genus comprises four species, all of which have been isolated from various marine environments, including marine animals, seawater, marine sediments, and seaweeds ( 1 4 ). The major characteristics among Agarivorans spp.…”
Section: Announcementmentioning
confidence: 99%
“…To date, four species under the genus Agarivorans have been identified: Agarivorans albus , Agarivorans gilvus , Agarivorans aestuarii , and Agarivorans litoreus ( 1 4 ). These are Gram-negative, aerobic bacteria known for their agar-degrading capacity, a feature that potentially influences the carbon cycle in marine ecosystems ( 1 4 ). We isolated Agarivorans sp.…”
Section: Announcementmentioning
confidence: 99%